A Systems study and procedures study on the Philippine Petroleum Corporation - Dela Vega, Geraldine; Galarosa, Iris Ann.; Mayoralgo, Anna Belen; Pira, Ma. Cristina; Senar, Racquel (Diliman, Quezon City College of Engineering, 1991)
This systems and procedures study introduces itself with the definition of the system- The Philippine Petroleum Corporation Shipping Department. It attempts at identifying the Problem Areas of the System along with the statement of the Objectives of the Department, specifications of the inputs to the system and the resulting end-products (States A and B). With the aim to culminate at a proper recommendation, the paper states the restrictions guiding the documentations toward this objective. Presentation and analysis of the existing system are stated in a detailed format. It begins with the analysis of the work distribution in the system, the system's procedures, the existing forms in the department, the lay-out of the forms and a general description. Proper critical examination is made on the analysis with the intention of coming up with alternatives for the problem areas. The alternatives are then evaluated, weighed with respect to some criteria and bounded by the stated restrictions. The recommendation in introduced into this paper with the definition of the solution.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Philippine Petroleum Corporation; Oil industries; Systems analysis